Multi-modal contributions to detoxification of acute pharmacotoxicity by a triglyceride micro-emulsion - Fettiplace, Michael R.; Lis, Kinga; Ripper, Richard; Kowal, Katarzyna; Pichurko, Adrian; Vitello, Dominic; Rubinstein, Israel; Schwartz, David; Akpa, Belinda S.; Weinberg, Guy (Journal of controlled release, 2015)
Triglyceride micro-emulsions such as Intralipid® have been used to reverse cardiac toxicity induced by a number of drugs but reservations about their broad-spectrum applicability remain because of the poorly understood mechanism of action. Herein we report an integrated mechanism of reversal of bupivacaine toxicity that includes both transient drug scavenging and a cardiotonic effect that couple to accelerate movement of the toxin away from sites of toxicity. We thus propose a multi-modal therapeutic paradigm for colloidal bio-detoxification whereby a micro-emulsion both improves cardiac output and rapidly ferries the drug away from organs subject to toxicity. In vivo and in silico models of toxicity were combined to test the contribution of individual mechanisms and reveal the multi-modal role played by the cardiotonic and scavenging actions of the triglyceride suspension. These results suggest a method to predict which drug toxicities are most amenable to treatment and inform the design of next-generation therapeutics for drug overdose. [Display omitted]